Effects of Vitamin D Supplementation and Seasonality on Circulating Cytokines in Adolescents: Analysis of Data From a Feasibility Trial in Mongolia - Yegorov, Sergey; Bromage, Sabri; Boldbaatar, Ninjin; Ganmaa, Davaasambuu (Frontiers in Nutrition, 2019)
Vitamin D deficiency is prevalent in human populations and has been linked to immune dysfunction. Here we explored the effects of cholecalciferol supplementation on circulating cytokines in severely vitamin D deficient (blood 25(OH)D << 30 nmol/L) adolescents aged 12-15 from Mongolia. The study included 28 children receiving 800 IU daily cholecalciferol for six months spanning winter and spring, and 30 children receiving placebo during the same period. The levels of 25(OH)D were assessed at baseline, three and six months. Twenty-one cytokines were measured in serum at baseline and at six months. Changes in 25(OH)D and cytokines were assessed using paired parametric tests. The median blood 25(OH)D concentration at baseline was 13.7 nmol/L (IQR=10.0-21.7). Supplementation tripled blood 25(OH)D levels (p<0.001) was associated with elevated interleukin (IL)-6 (p=0.043). The placebo group had reduced macrophage inflammatory protein (MIP)-1α (p=0.007) and IL-8 (p=0.034) at six months. Although limited by a small sample size, these findings suggest that cholecalciferol supplementation and seasonality may impact systemic immunity in adolescents, identifying chemokines as potentially important biomarkers of vitamin D status in this Northeast Asian population. Larger clinical trials are warranted to validate these results.